PEA (PISUM L.) ACCESSIONS DIFFER IN THE STAGE OF FLOWER DEVELOPMENT BEST FOR POLLINATION - O. E. Kosterin; V. S. Bogdanova (Вавиловский журнал генетики и селекции)
In order to optimize artificial pollination in various pea species and subspecies, the efficiency of artificial pollination was analyzed in eight accessions belonging to Pisum fulvum, Pisum sativum ssp. elatius (wild), P. abyssinicum, and P. sativum ssp. sativum (cultivated). Mean numbers of seeds per flower pollinated with its own pollen were determined in three pollination methods: 1) immediately after bud castration before anther dehiscence, 2) after the dehiscence of a flower castrated at the same stage (delayed pollination), and 3) double pollination as in methods (1) and (2). These methods did not differ in efficiency in cultivated accessions. In wild ones, method (2) was similar to (1) or better, whereas method (3) was comparable in efficiency with method (2). Method (2) (delayed pollination) was 12 times as efficient as method (1) in accession 721 (Pisum sativum subsp. elatius), possessing very large flowers. Delayed pollination is recommended for wild pea varieties.